The Minority Confederate Induced Errors of the Majority Members in the Role-Inverted Asch Experiment - Mori, Kazuo; Miyazawa, Satoru; Morioka, Yuta; Murayama, Takahiro (Advances in Social Sciences Research Journal, 2024)
This study aimed to investigate whether errors made by minority group members could influence the behavior of the majority in a role-reversed version of Asch's conformity experiment. Eighty-five undergraduate students, comprising 51 males and 34 females, were organized into groups of four individuals who were already acquainted with each other. From these groups, we randomly selected twelve, and discreetly instructed the third student in each group (a confederate) to provide incorrect responses on six out of the nine line-judgment tasks, similar to Asch's majority's behavior. The findings revealed that groups with the confederate member did lead to an increase in errors from other group members, although this increase did not reach statistical significance. Nevertheless, further analyses indicated that participants were more likely to make errors when other group members had already responded incorrectly. Consequently, we interpreted these errors as a form of social conformity, where participants intentionally made mistakes to alleviate the awkwardness of having only one member of the group providing incorrect answers. In summary, this study provides insights into the dynamics of social conformity and the impact of minority errors on group behavior in a role-reversed Asch experiment.